IASA Emerging Scholars: The Position of the IASA Executive Council on the Inclusion of Emerging Scholars in the Leadership of the Organization - Executive Council, IASA (Review of International American Studies, 2022)
The Statement of the IASA Executive Council on the Inclusion of Emerging Scholars in the Leadership of the Organization and the support of the Early Career Scholars.